Students' Poetry Writing Skills Through the Mind Mapping Method: A Remote Indonesian Elementary School - Martha Sendi Laurika; Zainudin Notanubun; Stelie D. Ratumanan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Poetry writing is a highly demanding literacy competency for young learners, yet conventional instruction in Indonesian elementary schools often lacks the necessary scaffolding. This collaborative classroom action research (CAR) study investigated whether the mind mapping method could enhance poetry writing ability by stimulating divergent thinking during the prewriting stage. Following the Kemmis and McTaggart spiral model, the intervention was conducted across two instructional cycles involving all 14 fifth-grade students at SD Inpres Naumatang, a remote public elementary school. Data were gathered through structured observations, documentation, and performance-based tests evaluated across three core rubrics: title, diction, and figurative language. The results demonstrated progressive improvement: the class mean rose from 61.10 (pre-test) to 66.00 (Cycle I), and ultimately to 73.29 (Cycle II). Crucially, classical mastery skyrocketed from 28.57% to 100.00% by the end of Cycle II. The most significant gains occurred in diction selection and figurative language, driven by optimized mind map exemplars, intensified individualized guidance, and enhanced thematic autonomy. This study extends the literature by applying mind mapping to the cognitively demanding domain of poetry in an under-researched remote-school context. It reframes mind mapping as a critical cognitive scaffold mediating divergent thinking and creative linguistic expressions, providing elementary educators with a replicable pedagogical sequence.